When the Learning Environment Is Suboptimal: Exploring Medical Students’ Perceptions of “Mistreatment” - Gan, Runye (Acad Med, 2014)
PURPOSE: Despite widespread implementation of policies to address mistreatment, high rates of mistreatment during clinical training are reported, prompting the question of whether “mistreatment” means more to students than delineated in official codes of conduct. Understanding “mistreatment” from students’ perspective and as it relates to the learning environment is needed before effective interventions can be implemented. METHOD: The authors conducted focus groups with final-year medical students at McGill University Faculty of Medicine in 2012. Participants were asked to characterize “suboptimal learning experience” and “mistreatment.” Transcripts were analyzed via inductive thematic analysis. RESULTS: Forty-one of 174 eligible students participated in six focus groups. Students described “mistreatment” as lack of respect or attack directed toward the person, and “suboptimal learning experience” as that which compromised their learning. Differing perceptions emerged as students debated whether “mistreatment” can be applied to negative learning environments as well as isolated incidents of mistreatment even though some experiences fell outside of the “official” label as per institutional policies. Whether students perceived “mistreatment” versus a “suboptimal learning experience” in negative environments appeared to be influenced by several key factors. A concept map integrating these ideas is presented. CONCLUSIONS: How students perceived negative situations during training appears to be a complex process. When medical students say “mistreatment,” they may be referring to a spectrum, with incident-based mistreatment on one end and learning-environment-based mistreatment on the other. Multiple factors influenced how students perceived an environment-based negative situation and may provide strategies to improving the learning environment.